2017
DOI: 10.1002/oby.21751
|View full text |Cite
|
Sign up to set email alerts
|

MTCH2 is a conserved regulator of lipid homeostasis

Abstract: MTCH2 is a conserved regulator of lipid homeostasis. MTCH2 was found to be both required and sufficient for lipid homeostasis shifts, suggesting that pharmacological inhibition of MTCH2 could be therapeutic for treatment of obesity and related disorders. MTCH2 could influence lipid homeostasis through inhibition of ESR1 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 42 publications
4
28
1
Order By: Relevance
“…2H) for further analysis as a candidate m 6 A gene in the regulation of intramuscular adipogenesis. Recent studies implicated MTCH2 in lipid accumulation and oxidation in mouse muscles (37) and Caenorhabditis elegans (38). In our study, we found that this gene exhibits relatively higher protein expression compared with L-LDM (P , 0.01) (Fig.…”
Section: Biologic Pathways Associated With M 6 A-modified Genessupporting
confidence: 65%
See 1 more Smart Citation
“…2H) for further analysis as a candidate m 6 A gene in the regulation of intramuscular adipogenesis. Recent studies implicated MTCH2 in lipid accumulation and oxidation in mouse muscles (37) and Caenorhabditis elegans (38). In our study, we found that this gene exhibits relatively higher protein expression compared with L-LDM (P , 0.01) (Fig.…”
Section: Biologic Pathways Associated With M 6 A-modified Genessupporting
confidence: 65%
“…Recent studies have reported that MTCH2 regulates lipid accumulation in mouse muscle and that its deficiency leads to an increase in whole-body energy utilization and protection against diet-induced obesity (37). In addition, MTCH2 overexpression enhanced lipid accumulation in C. elegans by inhibiting the transcriptional activation of estrogen receptor 1 (38). In the present study, we found that MTCH2 mRNA and protein levels were higher in Jinhua pigs compared with those in Landrace pigs, and that MTCH2 protein was positively associated with adipogenesis in porcine intramuscular preadipocytes in the first 2 d after MDI induction.…”
Section: Discussionmentioning
confidence: 99%
“…MTCH2 is a conserved regulator of lipid homeostasis. Knockdown of MTCH2/mtch2 reduced lipid accumulation (in adipocyte-like cells, C. elegans and mice) [ 15 ] and number of adipocytes (in zebrafish) [ 16 ], while overexpression of MTCH2 increased fat accumulation (in adipocyte-like cells, C. elegans and mice) [ 15 , 17 ]. Loss of muscle MTCH2 protected mice from diet-induced obesity and hyperinsulinemia and increased energy expenditure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of MTCH2 in the brain is unclear. MTCH2 is known to contribute to adipocyte function, regulation of lipid metabolism [40,42], and to be genetically associated with obesity [43]. However, MTCH2 clearly has a role outside of adipocytes, as inhibition of MTCH2 increases products of metabolism, such as pyruvate and pyruvate dehydrogenase [44] in both brain and muscle.…”
Section: Mtch2 Chr11mentioning
confidence: 99%
“…It is not tremendously unexpected that MTCH2 has a direct impact on neurological function as the brain is one of the most metabolically active organs in the body. MTCH2 knockout mice exhibited deficits in both metabolic processes and hippocampal dependent spatial learning tasks [42,45,46]. There are known links between nutrition, specifically cholesterol consumption levels, in AD [47], which can also present health risks for cardiovascular function, another wellknown risk factor for AD.…”
Section: Mtch2 Chr11mentioning
confidence: 99%